Legitimasi Kekuasaan Juraytuwe Di Desa Talang Sejemput Kecamatan Pulau Pinang Kabupaten Lahat - Wiwin Prabudiani; Dadang Hikmah Purnama; Happy Warsito (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2016)
This study aims to understand Juray tuwe legitimacy his power in Talang Sejemput Village. Specifically this study detailing the sources of power, mechanisms of using and maintaining sources of power, to explain social relations and political Juray Tuwe with rural communities, and explain the implications of power Juray Tuwe on politics and government, social and economic, as well as security and order in the village. This study used a qualitative design with intrinsic case study strategy. This research paradigm critism and approach is poststructuralism Michael Focault. Collecting data using the technique of participant observation, in-depth interviews, and documentation of literature. The results showed the legitimacy of power is very closely related to the sources of power, which is used as a reference in the mechanism of arranging the order of village and as a guide in making decisions on the behavior of the rural communities that are considered contrary to customary law. Maintenance of power sources is realized throughÂ a variety of actions, activities, and special ritual, so that its implementation can be accepted, recognized, and implemented in rural communities. The pattern of the relationship between Juray Tuwe by the village elite shows the mutual support ang complement, although the implementation of customs rules more dominant. Juray Tuweâ€™s power implications in the lives of rural communities capable of promoting the values of social cohesion and sustainable use of natural resources based on the needs of life.